2021
DOI: 10.5812/jjm.109676
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Susceptibility of Non-tuberculous Mycobacteria Isolated from Sputum Samples of Patients with Pulmonary Infections in China

Abstract: Background: Non-tuberculous mycobacteria (NTM) are widely associated with pulmonary diseases. Evidence is lacking on the transmission of NTM from one person to another. Hence, it has gained lower public health priority than tuberculosis. Objectives: We determined the prevalence and antibiotic resistance rate of NTM isolated from sputum samples of patients with pulmonary infections. Methods: A total of 375 duplicate sputum samples were collected from 375 patients on consecutive days. The NTM growth was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This study showed that the most common NTM isolates were M. fortuitum, followed by M. simiae, M. kansasii, M. gordonae, and M. conceptense. Aside from that, a variety of studies have been conducted on the prevalence of NTM infections, in particular M. avium-intracellulare (MAC) infection, M. abscessus, M. chelonae, M. fortuitum, and M. kansasii (Chiang et al 2021;Zhou et al 2021). Our study revealed that in the majority of cases, M. simiae, M. fortuitum, M. kansasii and M. marinum were detected.…”
Section: Discussionmentioning
confidence: 62%
“…This study showed that the most common NTM isolates were M. fortuitum, followed by M. simiae, M. kansasii, M. gordonae, and M. conceptense. Aside from that, a variety of studies have been conducted on the prevalence of NTM infections, in particular M. avium-intracellulare (MAC) infection, M. abscessus, M. chelonae, M. fortuitum, and M. kansasii (Chiang et al 2021;Zhou et al 2021). Our study revealed that in the majority of cases, M. simiae, M. fortuitum, M. kansasii and M. marinum were detected.…”
Section: Discussionmentioning
confidence: 62%